Intra-aortic balloon contrapulsation through subclavian access as a bridge to heart transplantation. Case report: - Ramirez Ramos, Cristhian Felipe (2021)
Advanced heart failure is a major health problem for which heart transplantation or left ventricular assist devices are the only effective treatments. Intra-aortic balloon pump inserted using femoral artery access as a bridge to heart transplantation is still frequently used, but has the disadvantage of limiting the patient’s movements, hence exposing him or her to the hazards of immobility and threatening the success of the procedure or hindering recovery. Access through the subclavian artery has become an attractive alternative since it doesn’t impair the patient’s mobility, and there is increasing evidence supporting its use. We present the first case of subclavian counterpulsation balloon implantation in a cardiovascular care center in Colombia.